Increase in the axial resistance of concrete walls for buildings through the application of Carbon Fiber Polymers - Bendezú R., Lenin (2024)
This experimental work hopes to provide a potential solution by proposing techniques to improve the axial resistance capacity of reinforced concrete walls, using high-strength carbon filaments, and proposing a practical methodology for reinforcing existing reinforced concrete columns and walls. The methodology used to improve this work consists of the exploration and experimentation of two explicit parts, the first being a progression of material tests carried out in the laboratories of the Pontificia Universidad Católica del Perú, with the purpose of determining the direct mechanical properties. and not direct. The second part of the work included the analysis of the reinforced concrete walls through the non-linear concept modeled with the finite element method, verifying the non-linear attributes of the concrete by increasing the high-resistance carbon fiber. The results found have been obtained using the Cypecad software, and show that, in the case of carbon fiber reinforced specimens, a moment of 20.50 (tonf-m) is reached with respect to an axial load of 125.13 (tonf). On the other hand, the specimen without reinforcement reaches a moment of 18.20 (tonf-m) with respect to an axial load of 104.76 (tonf).